Electrolyte and secondary battery

The electrolyte with 1,3-propane sultone and lithium difluorophosphate additives addresses the challenges of cycle performance and high-temperature storage in secondary batteries by forming protective films, reducing gas production, and stabilizing electrodes, thus enhancing battery performance.

CN119181857APending Publication Date: 2024-12-24GUANGZHOU TINCI MATERIALS TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411675784.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing secondary batteries face challenges in achieving high energy density, long cycle life, wide operating temperature range, and good rate characteristics, particularly in terms of cycle performance and high-temperature storage performance.

Method used

An electrolyte comprising a solvent, an electrolyte, and additives including a compound represented by formula I (1,3-propane sultone) and lithium difluorophosphate, with specific mass percentages, is used to form films at the electrodes, inhibiting gas production and improving volume expansion, thereby enhancing cycle performance and high-temperature storage performance.

Benefits of technology

The electrolyte formulation effectively reduces gas production, stabilizes electrodes under high temperatures, and improves the cycle performance and high-temperature storage performance of secondary batteries by forming protective films and promoting ion circulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181857A_ABST
    Figure CN119181857A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte and a secondary battery. The electrolyte comprises a solvent, an electrolyte and an additive, and the additive comprises a compound shown in a formula I, 1, 3-propane sultone and lithium difluorophosphate; based on the mass of the electrolyte, the mass percentage content of the compound shown in the formula I is A, and 0.1% < = A < = 10%; the mass percentage of 1, 3-propane sultone is B, and B is greater than or equal to 0.1% and less than or equal to 5%; the mass percentage of the lithium difluorophosphate is C, and C is more than or equal to 0.1% and less than or equal to 5%. Through the synergistic effect of the compound shown in the formula I, 1, 3-propane sultone and lithium difluorophosphate, the cycle performance and high-temperature storage performance of the secondary battery can be improved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to an electrolyte and a secondary battery. Background Art

[0002] In recent years, with the rapid development and widespread application of various portable electronic devices, new energy electric vehicles and energy storage systems, the demand for secondary batteries with high energy density, long cycle life, wide operating temperature range and good rate characteristics has become increasingly urgent.

[0003] As the conductive carrier of ions between the positive and negative electrodes of secondary batteries, the electrolyte is critical to the performance of secondary batteries. Therefore, it is urgent to develop more comprehensive electrolytes to improve the cycle performance and high-temperature storage performance of secondary batteries. Summary of the invention

[0004] The purpose of this application is to provide an electrolyte and a secondary battery to improve the cycle performance and high temperature storage performance of the secondary battery. The specific technical solution is as follows: The first aspect of the present application provides an electrolyte, which includes a solvent, an electrolyte and an additive, wherein the additive includes a compound represented by formula I, 1,3-propane sultone and lithium difluorophosphate; ; Wherein, based on the mass of the electrolyte, the mass percentage of the compound represented by formula I is A, 0.1%≤A≤10%; the mass percentage of 1,3-propane sultone is B, 0.1%≤B≤5%; the mass percentage of lithium difluorophosphate is C, 0.1%≤C≤5%; preferably, 0.1%≤A≤5%, 0.1%≤B≤2%, and 0.1%≤C≤2%.

[0005] In one embodiment of the present application, the mass ratio of the compound represented by formula I to the 1,3-propane sultone is m 1 The mass ratio m of the compound represented by formula I to the lithium difluorophosphate is 1 to 3:1; 2 It is 1~3:1.

[0006] In one embodiment of the present application, the additives also include other additives, and the other additives are selected from at least one of vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, ethylene sulfate, 1,3-propylene sultone, vinyl sulfite, tris(trimethylsilane)borate and tris(trimethylsilane)phosphate; based on the mass of the electrolyte, the mass percentage of the other additives is D, 0.5%≤D≤20%, preferably, 5%≤D≤10%.

[0007] In one embodiment of the present application, the electrolyte is selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium hexafluoroarsenate, lithium tetrafluoroborate and lithium bis(oxalatoborate); based on the mass of the electrolyte, the mass percentage of the electrolyte is E, 10%≤E≤20%.

[0008] In one embodiment of the present application, the solvent is selected from at least two of propylene carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, fluoroethylene carbonate, γ-butyrolactone, cyclopentane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate and butyl butyrate; based on the mass of the electrolyte, the mass percentage of the solvent is F, 65%≤F≤89%.

[0009] The second aspect of the present application provides a secondary battery, which includes a positive electrode plate, a negative electrode plate, a separator and the electrolyte described in the first aspect of the present application.

[0010] In one embodiment of the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes a silicon-based material; preferably, the silicon-based material is selected from at least one of a silicon-oxygen compound and a silicon-carbon composite.

[0011] In one embodiment of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes a nickel cobalt lithium manganese oxide ternary material; the molecular formula of the nickel cobalt lithium manganese oxide ternary material is LiNi a Co b Mn c O 2 , where a, b, c satisfy a+b+c=1.

[0012] In one embodiment of the present application, the operating voltage of the secondary battery is ≥4.4V.

[0013] Beneficial effects of this application: The present application provides an electrolyte and a secondary battery. The electrolyte of the present application includes a solvent, an electrolyte and an additive, wherein the additive includes a compound shown in formula I, 1,3-propane sultone and lithium difluorophosphate; based on the mass of the electrolyte, the mass percentage of the compound shown in formula I is A, 0.1%≤A≤10%; the mass percentage of 1,3-propane sultone is B, 0.1%≤B≤5%; the mass percentage of lithium difluorophosphate is C, 0.1%≤C≤5%. The mass percentages of the compound shown in formula I, 1,3-propane sultone and lithium difluorophosphate are limited within the scope of the present application. The compound shown in formula I helps to inhibit gas production, 1,3-propane sultone helps to form a film at the negative electrode and has good stability under high temperature conditions, and lithium difluorophosphate helps to form a film at the positive electrode and promotes circulation. The three can effectively improve the volume expansion of the negative electrode of the secondary battery, the dissolution of the positive electrode metal, and the serious gas production through synergistic effects, thereby helping to improve the cycle performance and high temperature storage performance of the secondary battery.

[0014] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION

[0015] The technical solution in this application will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. All other embodiments obtained by those skilled in the art based on this application belong to the scope of protection of this application.

[0016] The first aspect of the present application provides an electrolyte, which includes a solvent, an electrolyte and an additive, wherein the additive includes a compound represented by formula I, 1,3-propane sultone and lithium difluorophosphate; ; Wherein, based on the mass of the electrolyte, the mass percentage of the compound represented by Formula I is A, 0.1%≤A≤10%; the mass percentage of 1,3-propane sultone is B, 0.1%≤B≤5%; the mass percentage of lithium difluorophosphate is C, 0.1%≤C≤5%; preferably, 0.1%≤A≤5%, 0.1%≤B≤2%, 0.1%≤C≤2%. For example, based on the mass of the electrolyte, the mass percentage A of the compound represented by Formula I can be 0.1%, 0.5%, 1%, 3%, 5%, 8%, 10% or a range consisting of any two values ​​therein, the mass percentage B of 1,3-propane sultone can be 0.1%, 0.5%, 1%, 2%, 5% or a range consisting of any two values ​​therein, and the mass percentage C of lithium difluorophosphate can be 0.1%, 0.5%, 1%, 2%, 5% or a range consisting of any two values ​​therein. When the contents of the compound represented by Formula I, 1,3-propane sultone and lithium difluorophosphate are within the above range, the synergistic effect of the three can be exerted to improve the cycle performance and high-temperature storage performance of the secondary battery.

[0017] The compound shown in Formula I can effectively reduce the gas production of the system and can be used to reduce the high-temperature gas production problem of the system. However, when used alone, the DC resistance (DCR) is large, which has an adverse effect on the high-temperature cycle performance. Therefore, lithium difluorophosphate is added to compete with it for positive electrode film formation. The middle part of the compound shown in Formula I is an ethylene carbonate structure. In the electrode reaction, lithium difluorophosphate has a stronger oxidizing ability and a lower redox potential than ethylene carbonate, so it takes precedence over the compound shown in Formula I in positive electrode film formation. By competing, the amount of film formation of the compound shown in Formula I alone is reduced, its film thickness is weakened, and DCR is reduced, thereby compensating for the large disadvantage of DCR of the compound shown in Formula I. However, the combined use of the compound shown in Formula I and lithium difluorophosphate also brings new problems. Since the positive electrode film formation competition ability of the compound shown in Formula I is weaker than that of lithium difluorophosphate, the reaction time in the electrolyte becomes longer, and the sulfur element contained therein will form sulfide impurities during the battery reaction, causing damage to the effective substances of the negative electrode. Therefore, 1,3-propane sultone containing a similar thiolactone structure to the compound shown in Formula I is further added to inhibit its impurity damage. 1,3-propane sultone has a small steric hindrance and good solubility. Its fluidity in the electrolyte is better than that of the compound shown in Formula I with large steric hindrance. In the electrode reaction, it forms a film at the negative electrode before the compound shown in Formula I. At this time, the film formation of 1,3-propane sultone can effectively protect the negative electrode, thereby improving the high temperature stability. At the same time, since 1,3-propane sultone and the compound shown in Formula I contain similar thiolactone structures, the presence of intermolecular orientation forces will also cause the two to repel each other, further hindering the movement and decomposition of the sulfur-containing groups of the compound shown in Formula I. Finally, since the compound shown in Formula I has a large steric hindrance, if it reacts with the electrode first, it will hinder the flow of ions and weaken the electrode reaction efficiency. Lithium difluorophosphate and 1,3-propane sultone form a film at the electrode before it, which can effectively avoid such problems. Therefore, the three can effectively improve the volume expansion of the negative electrode of the secondary battery, the dissolution of the positive electrode metal, and the serious gas production through synergistic action, which is beneficial to improve the cycle performance and high temperature storage performance of the secondary battery.

[0018] In one embodiment of the present application, the mass ratio of the compound represented by formula I to the 1,3-propane sultone is m 1 The mass ratio m of the compound represented by formula I to the lithium difluorophosphate is 1 to 3:1; 2 1~3:1. Adjust m 1 and m 2 Within the above range, the synergistic effect of the three can be better exerted to further improve the cycle performance and high-temperature storage performance of the secondary battery.

[0019] In one embodiment of the present application, the additives also include other additives, and the other additives are selected from at least one of vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, ethylene sulfate, 1,3-propylene sultone, vinyl sulfite, tris(trimethylsilyl) borate and tris(trimethylsilyl) phosphate; based on the mass of the electrolyte, the mass percentage of the other additives is D, 0.5%≤D≤20%, preferably, 5%≤D≤10%. For example, based on the mass of the electrolyte, the mass percentage D of the other additives can be 0.5%, 1%, 5%, 10%, 15%, 20% or a range consisting of any two of the values. The electrolyte includes the above-mentioned other additives and regulates the mass percentage of other additives within the scope of the present application. Other additives (such as fluoroethylene carbonate) can improve the cycle performance of the secondary battery, reduce the film formation impedance, inhibit the expansion of the negative electrode and withstand high pressure. The synergistic effect between the four can further improve the cycle performance and high temperature storage performance of the secondary battery.

[0020] In one embodiment of the present application, the electrolyte is selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium hexafluoroarsenate, lithium tetrafluoroborate and lithium bis(oxalatoborate); based on the mass of the electrolyte, the mass percentage of the electrolyte is E, 10%≤E≤20%. The electrolyte includes the above electrolyte and regulates the mass percentage of the electrolyte within the scope of the present application, so that the electrolyte has higher ionic conductivity and good electrochemical stability, and can further improve the cycle performance and high temperature storage performance of the secondary battery.

[0021] In one embodiment of the present application, the solvent is selected from at least two of propylene carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, fluoroethylene carbonate, γ-butyrolactone, cyclopentane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate and butyl butyrate; based on the mass of the electrolyte, the mass percentage content of the solvent is F, 65%≤F≤89%. For example, based on the mass of the electrolyte, the mass percentage content F of the solvent can be 65%, 70%, 75%, 80%, 85%, 89% or a range consisting of any two of the values. The electrolyte includes the above-mentioned solvent, and by regulating the mass percentage of the solvent within the scope of the present application, the electrolyte can have a suitable viscosity, a higher ionic conductivity and good electrochemical stability, which can further improve the cycle performance and high-temperature storage performance of the secondary battery.

[0022] The present application has no particular restrictions on the preparation method of the electrolyte, as long as the purpose of the present application can be achieved. For example, various solvents in the electrolyte can be mixed, and then electrolytes and additives can be added and mixed evenly.

[0023] The second aspect of the present application provides a secondary battery, which includes a positive electrode plate, a negative electrode plate, a separator and the electrolyte described in the first aspect of the present application.

[0024] It should be noted that in the specific implementation of the present application, lithium-ion batteries are used as an example of secondary batteries to explain the present application, but the secondary batteries of the present application are not limited to lithium-ion batteries. The specific technical solutions are as follows: In one embodiment of the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes a silicon-based material. The theoretical capacity of silicon-based materials is high, which is conducive to improving the energy density of secondary batteries, but during the charging and discharging process of secondary batteries, as lithium ions are inserted and removed, the silicon-based materials will undergo a volume expansion of 120% to 300%. The use of the electrolyte provided by the present application is conducive to forming a solid electrolyte interface film with high mechanical strength, good stability, high ionic conductivity and high toughness at the negative electrode interface, which can effectively inhibit the rupture of the solid electrolyte interface film caused by the expansion of silicon-based materials, and reduce the side reactions caused by direct contact between the negative electrode active material and the electrolyte. In addition, the compound shown in formula I in the electrolyte provided by the present application helps to inhibit gas production, and 1,3-propane sultone helps to form a negative electrode film and has good stability under high temperature conditions, which can effectively improve the volume expansion of the negative electrode of the secondary battery, as well as the serious gas production and other problems, thereby improving the cycle performance and high temperature storage performance of the secondary battery.

[0025] The present application has no particular restrictions on silicon-based materials, as long as the purpose of the present application can be achieved. For example, the silicon-based material can be selected from but not limited to at least one of elemental silicon, silicon oxides, silicon carbon composites, silicon nitrogen composites, and silicon alloys. Preferably, the silicon-based material is selected from at least one of silicon oxides and silicon carbon composites. The negative electrode active material may also include a carbon-based material, which may be selected from but not limited to at least one of soft carbon, hard carbon, and graphite.

[0026] The above-mentioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its thickness direction, or on two surfaces of the negative electrode current collector along its thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the negative electrode current collector, or it can be a partial area of ​​the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.

[0027] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam or copper foam may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).

[0028] The present application has no particular limitation on the thickness of the negative electrode material layer and the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided negative electrode material layer is 8 μm to 10 μm, and the thickness of the negative electrode current collector is 5 μm to 10 μm.

[0029] In one embodiment of the present application, the negative electrode material layer may further include a conductive agent and a binder. The present application does not particularly limit the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of superconducting carbon black (Super P), acetylene black, Ketjen black, carbon nanotubes, graphene and carbon fibers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The binder may include but is not limited to at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode material layer. Those skilled in the art may select according to actual needs as long as the purpose of the present application can be achieved.

[0030] In one embodiment of the present application, the negative electrode material layer may further include a conductive agent, a binder and a thickener. The present application does not particularly limit the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, the conductive agent and the binder may be at least one of the above conductive agent and the above binder. The thickener may include but is not limited to at least one of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose. The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent, the binder and the thickener in the negative electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.

[0031] Optionally, the negative electrode plate may further include a conductive layer, and the conductive layer is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, and it may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, and it may be at least one of the above conductive agent and the above binder.

[0032] The present application has no particular restrictions on the preparation method of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the negative electrode active material, thickener, binder and conductive agent can be mixed in a certain mass ratio, and a solvent can be added and stirred evenly to obtain a negative electrode slurry with a solid content of 45wt% to 55wt%. The negative electrode slurry is evenly coated on one surface of the negative electrode current collector, and after drying, a negative electrode sheet coated with a negative electrode material layer on one side is obtained. Then, the above coating steps are repeated on the other surface of the negative electrode current collector, and after drying, a negative electrode sheet coated with a negative electrode material layer on both sides is obtained, which is then rolled, cut, and welded to the pole ears to obtain a negative electrode sheet.

[0033] In one embodiment of the present application, the compaction density of the negative electrode sheet is 1-3 g / cm 3 .

[0034] In one embodiment of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode material layer includes a positive electrode active material, and the positive electrode active material is selected from a ternary material including nickel cobalt lithium manganese oxide; the molecular formula of the nickel cobalt lithium manganese oxide ternary material is LiNi a Co b Mn c O 2 , where a, b, c satisfy a+b+c=1. For example, the nickel-cobalt-lithium-manganese oxide ternary material may include but is not limited to NCM613, NCM811, NCM622, and NCM523.

[0035] The above-mentioned “positive electrode material layer disposed on at least one surface of the positive electrode current collector” means that the positive electrode material layer can be disposed on one surface of the positive electrode current collector along its thickness direction, or on two surfaces of the positive electrode current collector along its thickness direction. It should be noted that the “surface” here can be the entire area of ​​the surface of the positive electrode current collector, or a partial area of ​​the surface of the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.

[0036] The present application has no particular restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the positive electrode current collector can be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil, aluminum alloy foil, nickel foil or nickel alloy can be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).

[0037] The present application has no particular limitation on the thickness of the positive electrode material layer and the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided positive electrode material layer is 15 μm to 18 μm, and the thickness of the positive electrode current collector is 10 μm to 20 μm.

[0038] The positive electrode material layer may also include a conductive agent and a binder. The present application does not particularly limit the types of conductive agents and binders, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of superconducting carbon black (SuperP), acetylene black, Ketjen black, carbon nanotubes, graphene and carbon fibers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The binder may include but is not limited to at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. The present application does not particularly limit the mass ratio of the positive active material, conductive agent and binder in the positive electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.

[0039] Optionally, the positive electrode sheet may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited, and it can be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, for example, it can be at least one of the above conductive agent and the above binder.

[0040] In one embodiment of the present application, the compaction density of the positive electrode sheet is 2-4 g / cm 3 .

[0041] The present application has no particular restrictions on the preparation method of the positive electrode sheet, as long as the purpose of the present application can be achieved, for example, the positive electrode active material, the conductive agent, and the binder are mixed in a certain proportion, and a solvent is added and stirred evenly to obtain a positive electrode slurry with a solid content of 50wt% to 75wt%. The positive electrode slurry is evenly coated on one surface of the positive electrode collector, and a positive electrode sheet coated with a positive electrode material layer on one side is obtained after drying. Then the above coating steps are repeated on the other surface of the positive electrode collector, and a positive electrode sheet coated with a positive electrode material layer on both sides is obtained after drying, and then rolled, cut, and welded to the pole ears to obtain a positive electrode sheet.

[0042] The present application has no particular restrictions on the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator can be selected from but not limited to at least one of ceramic, polyethylene (PE), polypropylene (PP), glass fiber, polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI) and polyamide (PA). The type of separator can include at least one of woven membrane, non-woven fabric, microporous membrane, composite membrane, rolled membrane and spun membrane.

[0043] In the present application, there is no particular limitation on the thickness of the separator, as long as the purpose of the present application can be achieved. For example, the thickness of the separator may be 10 μm to 20 μm.

[0044] In one embodiment of the present application, the operating voltage of the secondary battery is ≥ 4.4 V. A high operating voltage of a secondary battery is beneficial to improving energy density, but a high operating voltage leads to a higher temperature of the secondary battery during charging, which may cause problems such as gas production and increased impedance. The use of the electrolyte provided by the present application can effectively improve problems such as severe gas production and increased impedance, thereby helping to improve the high-temperature cycle performance and high-temperature storage performance of the secondary battery.

[0045] In the present application, the secondary battery also includes a shell for accommodating a positive electrode plate, a separator, a negative electrode plate and an electrolyte, as well as other components known in the field of secondary batteries, and the present application does not limit the above-mentioned other components. The present application has no special restrictions on the shell, and it can be a shell known in the art, as long as the purpose of the present application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and the present application does not limit the type of metal. A metal hard shell known in the art can be used, as long as the purpose of the present application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.

[0046] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and there is no particular limitation in the present application. For example, the preparation process of the secondary battery may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding and folding them as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and encapsulating, standing, forming, shaping, sorting and other processes to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.

[0047] Example Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.

[0048] Test methods and equipment: High temperature storage performance test The lithium-ion battery was placed in a 60°C constant temperature box, left to stand for 6 hours, charged to 4.4V at 1.0C constant current, then charged to a cut-off current of 0.05C at 4.4V constant voltage, left to stand for 30 minutes, discharged to 2.75V at 1.0C constant current, then charged to 4.4V at 1.0C constant current, then charged to a cut-off current of 0.05C at 4.4V constant voltage, left to stand for 30 minutes, discharged to 2.75V at 1.0C constant current, recorded as the initial capacity C 1 Then charge the lithium-ion battery at a constant current of 1.0C to a voltage of 4.4V, and then charge it at a constant voltage of 4.4V to a cut-off current of 0.05C. Suspend the lithium-ion battery with a thin wire and immerse it in a container filled with water. Record the reading of the balance at this time as m 1 The lithium-ion battery was then placed at 60°C for 7 days, 30 days, and 60 days. At the above time points, the lithium-ion battery was taken out and discharged at a constant current of 1.0C until the voltage reached 2.75V. The discharge capacity was recorded as C 2 ; Then charge the lithium-ion battery at a constant current of 1.0C to a voltage of 4.4V, and then charge it at a constant voltage of 4.4V to a cut-off current of 0.05C, and record the charging capacity as C 3 , and test DCR, again suspend the lithium-ion battery with a thin wire and immerse it in a container filled with water, and record the reading of the balance as m 2 The charge and discharge cycle test instrument is Xinwei BTS.

[0049] Storage capacity recovery rate R 1 (%) = C 3 / C 1 ×100%; Storage capacity retention rate R 2 (%) = C2 / C 1 ×100%; The gas production △V (mL) was measured by drainage method, △V = (m 2 -m 1 ) / ρ, where ρ is the density of liquid water.

[0050] High temperature cycle performance test Place the lithium-ion battery in a 45°C constant temperature box and let it stand for 5 minutes. Then charge the lithium-ion battery at a constant current of 1.0C to a voltage of 4.4V, then charge it at a constant voltage of 4.4V to a current of 0.05C, let it stand for 30 minutes, and then discharge it at a constant current of 1.0C to a voltage of 2.75V. Record the initial discharge capacity as C. 4 This is considered a charge-discharge cycle. Repeat the above charge-discharge cycle to 500 times, and record the discharge capacity after the 200th, 300th, and 500th cycles as C 5 , C 6 , C 7 ; 45℃ charge and discharge cycle 200 times capacity retention rate (%) = C 5 / C 4 ×100%, 45℃ charge and discharge cycle 300 times capacity retention rate (%) = C 6 / C 4 ×100%, 45℃ charge and discharge cycle 500 times capacity retention rate (%) = C 7 / C 4 ×100%. The charge and discharge cycle test instrument is Xinwei BTS.

[0051] Normal temperature cycle performance test Place the lithium-ion battery in a 25℃ constant temperature box and let it stand for 5 minutes. Then charge the lithium-ion battery at a constant current of 1.0C to a voltage of 4.4V, then charge it at a constant voltage of 4.4V to a current of 0.05C, let it stand for 30 minutes, and then discharge it at a constant current of 1.0C to a voltage of 2.75V. Record the initial discharge capacity as C. 8 This is considered a charge-discharge cycle. Repeat the above charge-discharge cycle to 500 times, and record the discharge capacity after the 200th, 300th, and 500th cycles as C 9 , C 10 , C 11 ; 25℃ charge and discharge cycle 200 times capacity retention rate (%) = C 9 / C 8 ×100%, 25℃ charge and discharge cycle 300 times capacity retention rate (%) = C 10 / C 8 ×100%, 25℃ charge and discharge cycle 500 times capacity retention rate (%) = C 11 / C 8×100%. The charge and discharge cycle test instrument is Xinwei BTS.

[0052] Example 1-1 <Preparation of Electrolyte> In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), solvents ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 3:3:4:10, and then the compound shown in formula I, 1,3-propane sultone and lithium difluorophosphate were added and mixed evenly, and then the electrolyte lithium hexafluorophosphate (LiPF 6 ), dissolved and mixed evenly to obtain an electrolyte; wherein, based on the mass of the electrolyte, LiPF 6 The mass percentage content is 13%, the mass percentage content A of the compound represented by formula I is 0.1%, the mass percentage content B of 1,3-propane sultone is 0.8%, the mass percentage content C of lithium difluorophosphate is 1%, and the balance is solvent.

[0053] <Preparation of positive electrode sheet> The positive electrode active material NCM613 (Zhenhua / 6000A), the conductive agent superconducting carbon black (Super P), carbon nanotubes (CNT, Tiannai LB107-44), and the binder polyvinylidene fluoride (PVDF, Solvay 5130) were mixed in a mass ratio of 95:3:0.5:1.5, and N-methylpyrrolidone (NMP) was added to prepare a slurry with a solid content of 68wt%, and stirred under the action of a vacuum mixer to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 16μm, and the mixture was heated at different temperature gradients (in order of After baking in an oven at 90℃, 100℃, and 85℃ at a speed of 2200mm / min, a positive electrode sheet coated with a positive electrode material layer on one side was obtained; then the above steps were repeated on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides; then, after rolling, slitting, and welding the pole ears, a positive electrode sheet with a specification of 258mm×315mm was obtained; wherein, the thickness of the single-sided positive electrode material layer was 16μm, and the compaction density of the positive electrode sheet was 3.4g / cm 3 .

[0054] <Preparation of negative electrode sheet> The negative electrode active material is graphite, silicon carbon composite (Zi Chen 550-M5-230415), conductive agent superconducting carbon black (Super P), binder styrene butadiene rubber (SBR, JSR-104A), thickener sodium carboxymethyl cellulose (CMC, crt30000PA) according to the mass ratio of 94.94:1.5:2:1.5:0.06, and CNT solvent is added to prepare a slurry with a solid content of 49wt%, and stirred under the action of a vacuum mixer to obtain a negative electrode slurry; The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 9μm, and the mixture is stirred at different temperature gradients (depending on the temperature of the negative electrode). After baking in an oven at 90°C, 100°C, and 85°C (for the third time) at a speed of 2200mm / min, a negative electrode sheet coated with a negative electrode material layer on one side was obtained; then the above steps were repeated on the other surface of the copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides; then, after rolling, slitting, and welding the pole ears, a negative electrode sheet with a specification of 258mm×300mm was obtained; wherein, the thickness of the single-sided negative electrode material layer was 9μm, and the compaction density of the negative electrode sheet was 1.6g / cm 3 .

[0055] <Preparation of Separator> A double-layer PP ceramic with a thickness of 16 μm was used as the diaphragm.

[0056] <Preparation of lithium-ion batteries> The positive electrode sheet, separator and negative electrode sheet prepared above are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound, the positive electrode ear is connected to the positive electrode sheet, and the negative electrode ear is connected to the negative electrode sheet to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, and the water is removed at 80°C, and the electrolyte prepared above is injected. After vacuum packaging, standing, forming, shaping, and sorting, a lithium-ion battery is obtained. Among them, the upper limit voltage of the formation is 4.4V, the formation temperature is 45°C, and the formation standing time is 25 minutes.

[0057] Example 1-2 to Example 1-13 Except that the mass percentage of the compound shown in Formula I, 1,3-propane sultone and lithium difluorophosphate is adjusted according to Table 1 in <Preparation of Electrolyte>, the mass percentage of the solvent is changed accordingly, and the percentage of other components in the electrolyte remains unchanged, the rest is the same as Example 1-1.

[0058] Example 2-1 to Example 2-4 In addition to adding other additives as shown in Table 2 in <Preparation of Electrolyte>, and adjusting the types and mass percentages of other additives according to Table 2, the mass percentage of the solvent changes accordingly, and the percentages of other components in the electrolyte remain unchanged, the rest is the same as Example 1-2.

[0059] Comparative Examples 1 to 6 Except that the mass percentage of the compound shown in Formula I, 1,3-propane sultone and lithium difluorophosphate is adjusted according to Table 1 in <Preparation of Electrolyte>, the mass percentage of the solvent is changed accordingly, and the percentage of other components in the electrolyte remains unchanged, the rest is the same as Example 1-1.

[0060] Comparative Example 7 to Comparative Example 8 The preparation method is the same as Example 1-1 except that the compound of Formula I is not added in <Preparation of Electrolyte>, the mass percentage of 1,3-propane sultone and lithium difluorophosphate is adjusted according to Table 1, the mass percentage of the solvent is changed accordingly, and the percentage of other components in the electrolyte remains unchanged.

[0061] Comparative Example 9 to Comparative Example 10 The preparation method is the same as Example 1-1 except that 1,3-propane sultone is not added in <Preparation of Electrolyte>, the mass percentage of the compound represented by Formula I and lithium difluorophosphate are adjusted according to Table 1, the mass percentage of the solvent is changed accordingly, and the percentage of other components in the electrolyte remains unchanged.

[0062] Comparative Example 11 to Comparative Example 12 The preparation method is the same as Example 1-1 except that lithium difluorophosphate is not added in <Preparation of Electrolyte>, the mass percentage of the compound shown in Formula I and 1,3-propane sultone is adjusted according to Table 1, the mass percentage of the solvent is changed accordingly, and the percentage of other components in the electrolyte remains unchanged.

[0063] Comparative Example 13 to Comparative Example 14 The preparation method is the same as Example 1-1 except that lithium difluorophosphate and 1,3-propane sultone are not added in <Preparation of Electrolyte>, the mass percentage of the compound represented by Formula I is adjusted according to Table 1, the mass percentage of the solvent changes accordingly, and the percentages of other components in the electrolyte remain unchanged.

[0064] Comparative Example 15 to Comparative Example 16 The preparation method is the same as Example 1-1 except that the compound represented by Formula I and lithium difluorophosphate are not added in <Preparation of Electrolyte>, the mass percentage of 1,3-propane sultone is adjusted according to Table 1, the mass percentage of the solvent is changed accordingly, and the percentages of other components in the electrolyte remain unchanged.

[0065] Comparative Example 17 to Comparative Example 18 The preparation method is the same as Example 1-1 except that the compound represented by Formula I and 1,3-propane sultone are not added in <Preparation of Electrolyte>, the mass percentage of lithium difluorophosphate is adjusted according to Table 1, the mass percentage of the solvent is changed accordingly, and the percentages of other components in the electrolyte remain unchanged.

[0066] Comparative Example 19 Except that the compound represented by formula I, 1,3-propane sultone and lithium difluorophosphate are not added in <Preparation of electrolyte>, the mass percentage of the solvent changes accordingly, and the percentage of other components in the electrolyte remains unchanged, the rest is the same as Example 1-1.

[0067] The preparation parameters of each embodiment and comparative example are shown in Tables 1 and 2, and the performance parameters are shown in Tables 3 and 4.

[0068] Table 1

[0069] In Table 1, “ / ” indicates no relevant parameters.

[0070] Table 2

[0071] In Table 2, “ / ” indicates no relevant parameters.

[0072] Table 3

[0073] Table 4

[0074] It can be seen from Examples 1-1 to 1-13 and Comparative Examples 1 to 19 that the electrolyte without adding the compound represented by Formula I, 1,3-propane sultone or lithium difluorophosphate is applied to the lithium ion battery, or the compound represented by Formula I, 1,3-propane sultone or lithium difluorophosphate is not within the scope of the present application, and the lithium ion battery has a lower storage capacity recovery rate and storage capacity retention rate when stored at 45°C for 7 days, 30 days and 60 days, as well as a higher gas production and DCR (Table 3); at the same time, the lithium ion battery has a lower capacity retention rate when charged and discharged at 25°C and 45°C for 200, 300 and 500 times (Table 4). The electrolyte to which the compound shown in Formula I, 1,3-propane sultone and lithium difluorophosphate are added simultaneously is applied to a lithium-ion battery, and the contents of the compound shown in Formula I, 1,3-propane sultone and lithium difluorophosphate are regulated within the scope of this application. The lithium-ion battery has a high storage capacity recovery rate and storage capacity retention rate when stored at 45°C for 7 days, 30 days and 60 days, as well as a low gas production and DCR (Table 3); at the same time, the lithium-ion battery has a high capacity retention rate when the charge and discharge cycles are 200, 300 and 500 times at 25°C and 45°C (Table 4). The above results illustrate that the compound shown in Formula I, 1,3-propane sultone and lithium difluorophosphate are used in combination in the electrolyte, and the contents of the compound shown in Formula I, 1,3-propane sultone and lithium difluorophosphate are limited within the scope of this application. The three components work synergistically to improve the cycle performance and high-temperature storage performance of the lithium-ion battery.

[0075] From Example 2-1 to Example 2-4, it can be seen that the electrolyte to which the compound shown in Formula I, 1,3-propane sultone, lithium difluorophosphate and fluoroethylene carbonate are added at the same time is applied to a lithium-ion battery, and the lithium-ion battery has a higher storage capacity recovery rate and storage capacity retention rate when stored at 45°C for 7 days, 30 days and 60 days, as well as a lower gas production and DCR (Table 3); at the same time, the lithium-ion battery has a higher capacity retention rate when the charge and discharge cycles are 200, 300 and 500 times at 25°C and 45°C (Table 4). The above results illustrate that the compound shown in Formula I, 1,3-propane sultone, lithium difluorophosphate and fluoroethylene carbonate are used in combination in the electrolyte, and the contents of the compound shown in Formula I, 1,3-propane sultone, lithium difluorophosphate and fluoroethylene carbonate are limited within the scope of this application, and the four components work synergistically to further improve the cycle performance and high temperature storage performance of the lithium-ion battery.

[0076] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. An electrolyte comprising a solvent, an electrolyte and an additive, wherein the additive comprises a compound represented by formula I, 1,3-propane sultone and lithium difluorophosphate; ; in, Based on the mass of the electrolyte, the mass percentage of the compound represented by formula I is A, 0.1%≤A≤10%; the mass percentage of 1,3-propane sultone is B, 0.1%≤B≤5%; and the mass percentage of lithium difluorophosphate is C, 0.1%≤C≤5%.

2. The electrolyte according to claim 1, wherein 0.1%≤A≤5%, 0.1%≤B≤2%, 0.1%≤C≤2%.

3. The electrolyte according to claim 1, wherein The mass ratio m1 of the compound represented by formula I to the 1,3-propane sultone is 1-3:1; the mass ratio m2 of the compound represented by formula I to the lithium difluorophosphate is 1-3:

1.

4. The electrolyte according to claim 1, wherein The additives also include other additives, and the other additives are selected from at least one of vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, ethylene sulfate, 1,3-propylene sultone, vinyl sulfite, tris(trimethylsilyl)borate and tris(trimethylsilyl)phosphate; based on the mass of the electrolyte, the mass percentage of the other additives is D, 0.5%≤D≤20%.

5. The electrolyte according to claim 1, wherein The electrolyte is selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium hexafluoroarsenate, lithium tetrafluoroborate and lithium bis(oxalatoborate); based on the mass of the electrolyte, the mass percentage of the electrolyte is E, 10%≤E≤20%.

6. The electrolyte according to claim 1, wherein The solvent is selected from at least two of propylene carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, fluoroethylene carbonate, γ-butyrolactone, cyclopentane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate and butyl butyrate; based on the mass of the electrolyte, the mass percentage of the solvent is F, 65%≤F≤89%. 7 . A secondary battery comprising a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte according to claim 1 .

8. The secondary battery according to claim 7, wherein The negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes a silicon-based material.

9. The secondary battery according to claim 7, wherein The positive electrode plate comprises a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode material layer comprises a positive electrode active material, wherein the positive electrode active material comprises a nickel-cobalt-lithium manganese oxide ternary material; the molecular formula of the nickel-cobalt-lithium manganese oxide ternary material is LiNi a Co b Mn c O2, where a, b, c satisfy a+b+c=1.

10. The secondary battery according to claim 7, wherein The operating voltage of the secondary battery is ≥4.4V.

Citation Information

Patent Citations

  • Manganese-rich lithium ion battery

    CN115207442A

  • Electrolyte of secondary battery, secondary battery and electronic device

    CN118867399A